(untitled) (Revista Paradigma, 2022)
The paper focuses on the dynamics of judicial precedents and the contemporary role of exceptional resources and autonomous actions to challenge judicial decisions in the Code of Civil Procedure of 2015. The strong emphasis given by the code to uniform jurisprudence and the linking of judicial precedents reflection on the ways of controlling judicial activity in its application. In this context, it is necessary to re-read autonomous actions of challenge, such as rescission and complaint, not only as a way of challenging decisions in their traditional sense, but also as a suitable means for control in the application of the precedent binding system all levels of jurisdiction. The work has, therefore, as main scope, to analyze normatively the contemporary function attributed to the forms of control judicial decisions in the Brazilian procedure. Considering that these are reflections about partial research results in progress, the methodology used will be bibliographic research.